2007
DOI: 10.1002/mds.21586
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nonmotor symptoms in Parkinson's disease in an international setting; Study using nonmotor symptoms questionnaire in 545 patients

Abstract: 2006, there was, no single instrument (questionnaire or scale) for attempting a comprehensive assessment of the wide range of nonmotor symptoms (NMS) of Parkinson's disease (PD). The PD nonmotor group, a multidisciplinary group of experts including patient group representatives developed and validated the NMS screening questionnaire (NMSQuest) comprising 30 items. The NMSQuest is a self completed screening tool designed to draw attention to the presence of NMS. In this paper, we present the results gathered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
299
5
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(359 citation statements)
references
References 14 publications
45
299
5
10
Order By: Relevance
“…In our study, a negative association was found between H&Y staging and MMSE while a positive association was found between Blessed test. 18 . Clinical presence and severity of autonomous involvement in PD is assessed effectively and correctly by using SCOPA-AUT questionnaire 8 .…”
Section: Resultsmentioning
confidence: 99%
“…In our study, a negative association was found between H&Y staging and MMSE while a positive association was found between Blessed test. 18 . Clinical presence and severity of autonomous involvement in PD is assessed effectively and correctly by using SCOPA-AUT questionnaire 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, autonomic dysfunction prese ts i the latter stages of Parki so 's disease [12] but it can occur early and even before the hallmark motor dysfunction presents [13]. The proposed mechanisms of cardiovascular autonomic dysfunction in Parki so 's disease generally involve lewy body accumulation and cell loss in various key areas of the autonomic nervous system, such as, autonomic regulatory areas including the hypothalamus, medulla, locus coeruleus and raphe, pre-ganglionic parasympathetic and sympathetic regions including the dorsal vagal motor nuclei of the glossopharyngeal and vagal nerves, autonomic and sympathetic ganglia, as well as post-ganglionic sympathetic denervation [1] that ultimately affect control of blood pressure through baroreflex impairment and loss of sympathetic innervation.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have shown that about 50% of PD patients have insomnia complaints [16,17]. Both motor and non-motor symptoms may be responsible for the insomnia.…”
Section: Sleep Disordersmentioning
confidence: 99%